Strategies of Islamic Education Teachers in Overcoming Students Difficulties in Reading the Qur'an at SMA Negeri 5 Kendari - Kiki Wahyudi; Raehang, Raehang (IAIN KENDARI, 2025)
This research aims to determine the strategies of Islamic Religious Education teachers in overcoming difficulties in reading the Koran for students at SMA Negeri 5 Kendari. This type of research uses descriptive qualitative. The research location is SMA Negeri 5 Kendari, Jl. Brigadier General Katamso, Baruga, District. Baruga, Kendari City. The data and data sources consist of primary and secondary data. As well as data collection techniques through observation, interviews and documentation. The technical data analysis is through data collection, data reduction and data presentation. The triangulation used is source triangulation and technical triangulation. The results of this research are the strategies used by Islamic Religious Education teachers in overcoming students' difficulties in reading the Koran at SMA Negeri 5 Kendari, including the teacher using the strategy (Sorogan) of reading the Koran one by one at the beginning of learning orintroduction. memorization tasks, and Rohis strategies.The methods used are the Qira'ati method, iqro method,peer tutoring method, and joint tadarus. The factorscausing students' difficulty in reading the Koran at SMANegeri 5 Kendari are internal factors, namely students'laziness in learning, and external factors, namely family factors and friendship environment.